Variations on An Episode of Facundo. Authors in Process: Domingo F. Sarmiento, José M. Paz and Eduarda Mansilla - Dellarciprete, Rubén (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The following writing starts off the reading of an anecdote starring Facundo Quiroga and told by Sarmiento in the chapter "The citadel" of his book Facundo. The anecdote of the civil wars of the mid-nineteenth century accumulates more than one version about episodes that have similar characteristics, a framework that allowed us to approach the sequence as a corpus of study. José María Paz in his Memoirs and Eduarda Mansilla in Pablo or life in the pampas, take up the anecdote of Sarmiento but alternate the characters that interpret it while enabling conflicting readings. On the other hand, we will also carry out a survey of the author's condition, mainly when we approach the textual and pictorial sources of the sarmientina script.